2017
DOI: 10.22211/cejem/69299
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of 3,3'-Dinitro-5,5'-Diamino-Bi-1,2,4-Triazole and Its Thermal Decomposition Study

Abstract: 3,3'-Dinitro-5,5'-diamino-bi-1,2,4-triazole (DABNT) was synthesized by a facile method and its crystalline density was determined as 1.839 g·cm −3 at 293(2) K by X-ray diffraction. Its thermal decomposition kinetics and mechanism were studied by means of differential scanning calorimetry-thermogravimetry (DCS-TG), in situ thermolysis by rapid-scan Fourier transform infrared spectroscopy (RSFTIR) and simultaneous TG-IR technology. The results showed that the apparent activation energies obtained by the Kissinge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Organic compounds containing a core structural component of 1,2,4-triazole as the extremely good scaffold were reported to possess inter alia the important relevance as pharmaceutics in a common use from various therapeutic classes [2,3] as well as energetic materials [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. There are some scientific papers focussed on the thermal properties of pharmacologically active molecules possessing the 1,2,4-triazole skeleton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic compounds containing a core structural component of 1,2,4-triazole as the extremely good scaffold were reported to possess inter alia the important relevance as pharmaceutics in a common use from various therapeutic classes [2,3] as well as energetic materials [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. There are some scientific papers focussed on the thermal properties of pharmacologically active molecules possessing the 1,2,4-triazole skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of other researchers [4][5][6][7][8][9][10][11][12][13] were mainly focussed on the thermal properties and decomposition processes of various energetic materials with the 1,2,4-triazole skeleton. Another scientific investigations [14][15][16] were aimed at assessing the range of thermal stability, phase-transition and decomposition temperatures of nitrogen-rich energetic materials bearing in their hybrid structures the 1,2,4-triazole scaffold combined with an additional azole ring such as the 1,2,3-triazole, 1,2,4-triazole or 1,2,4-tetrazole. In turn, Yan et al [17] investigated the thermal properties of nitrogen-rich 1,2,4-triazole-1,2,4,5-tetrazine-1,2,4-triazole hybrids as highly stable energetic materials and identified their thermolysis products.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that decomposition temperature of these polymers is under 350 °C. Moreover, triazole linkages is present in many organic compounds requiring high temperatures for decomposition, such as 3,3′-dinitro-5,5′-diamino-bi-1,2,4-triazole, which decomposes at 275.5 °C with a heating rate of 5 K·min −1 [ 63 ]. In general, 1,2,3-triazole moiety decomposes at 300–400 °C [ 64 ], but the exact temperature of decomposition is always dependent on the structure of attached molecules because some moieties can decrease their stability.…”
Section: Deactivation Routes Of Diazonium-based Catalystsmentioning
confidence: 99%
“…With increasing demands for high-energy-density materials (HEDMs), polynitro heterocyclic compounds have attracted considerable attention owing to their excellent detonation performances, good thermal stability, and low impact sensitivity. Recently, many polynitro heterocyclic compounds have been synthesized, such as 3,3′-dinitrimino-5,5′-bis­(1 H -1,2,4-triazole) (DNABT), , 5,5′-dinitro-3,3′-bis-1,2,4-triazole (DNBT), 3,3′-dinitromethyl-5,5′-bis­(1,2 H -1,2,4-triazole) (DNMBT), 5-(5-nitrimino-1,3 H -1,2,4-triazole-3-yl)-3-nitro-1 H -1,2,4-triazole (NNBT), 3,3′-dinitro-5,5′-bis-1,2,4-triazole-1,1′-diol (DNBTO), 1,1′-diamino-3,3′-dinitro-5,5-bis-1,2,4-triazole (DABNT), 3,3′-diamino-4,4′-dinitramino-5,5′-bis-1,2,4-triazole (H 2 ANAT), and so on. These compounds possess aromatic ring skeletons and plenty of -NO 2 groups which can improve their stability and release more energy.…”
Section: Introductionmentioning
confidence: 99%